Subaqueous shrinkage cracks in the Sheepbed mudstone: Implications for early fluid diagenesis, Gale crater, Mars. Issue 7 (17th July 2014) - Siebach, K. L.; Grotzinger, J. P.; Kah, L. C.; Stack, K. M.; Malin, M.; Léveillé, R.; Sumner, D. Y.
Abstract The Sheepbed mudstone, Yellowknife Bay formation, Gale crater, represents an ancient lakebed now exhumed and exposed on the Martian surface. The mudstone has four diagenetic textures, including a suite of early diagenetic nodules, hollow nodules, and raised ridges and later diagenetic light‐toned veins that crosscut those features. In this study, we describe the distribution and characteristics of the raised ridges, a network of short spindle‐shaped cracks that crosscut bedding, do not form polygonal networks, and contain two to four layers of isopachous, erosion‐resistant cement. The cracks have a clustered distribution within the Sheepbed member and transition laterally into concentrations of nodules and hollow nodules, suggesting that these features formed penecontemporaneously. Because of the erosion‐resistant nature of the crack fills, their three‐dimensional structure can be observed. Cracks that transition from subvertical to subhorizontal orientations suggest that the cracks formed within the sediment rather than at the surface. This observation and comparison to terrestrial analogs indicate that these are syneresis cracks—cracks that formed subaqueously. Syneresis cracks form by salinity changes that cause sediment contraction, mechanical shaking of sediment, or gas production within the sediment. Examination of diagenetic features within the Sheepbed mudstone favors a gas production mechanism, which has been shown to create a variety of diagenetic morphologies comparable to the raised ridges and hollow nodules. The crack morphology and the isopachous, layered cement fill show that the cracks were filled in the phreatic zone and that the Sheepbed mudstone remained fluid saturated after deposition and through early burial and lithification.